SOSIALISASI DAN EDUKASI MASYARAKAT CIOMAS TERHADAP BAHAYA SAMPAH PLASTIK - Arif Hidayatullah; Syaiful Syaiful; Asri Kusuma Wardhani (JPMUJ, 2025)
Efforts to reduce the use of plastic and Styrofoam in order to avoid environmental pollution by plastic waste, the Regional Government of Bogor Regency stipulates Bogor Regent Regulation Number 13 of 2019 concerning Reducing The Use Of Plastic And Styrofoam in order to increase public awareness to create a well-maintained and sustainable environment that the use of plastic and Styrofoam Styrofoam has become a serious problem in Indonesia and especially in Bogor Regency because of its nature that is difficult to decompose, so in addition to managing plastic waste, its use must also be limited. This study aims to educate the ciomas community about the dangers of plastic waste in order to further limit the use of plastic in their daily life.